Long-term effects of mobile exoneuromusculoskeleton (ENMS)-assisted self-help telerehabilitation after stroke - Qing, Wanyi; Nam, Ching-Yi; Shum, Harvey Man-Hok; Chan, Marko Ka-Leung; Yu, King-Pong; Ng, Serena Sin-Wah; Yang, Bibo; Hu, Xiaoling (Frontiers in Neuroscience, 2024)
Investigation on long-term effects of robot-assisted poststroke rehabilitation is challenging because of the difficulties in administration and follow-up of individuals throughout the process. A mobile hybrid neuromuscular electrical stimulation (NMES)-robot, i.e., exoneuromusculoskeleton (ENSM) was adopted for a single-group trial to investigate the long-term effects of the robot-assisted self-help telerehabilitation on upper limb motor function after stroke. Twenty-two patients with chronic stroke were recruited to attend a 20-session telerehabilitation program assisted by the wrist/hand module of the ENMS (WH-ENMS). Participants were evaluated before, after, as well as at 3 months and 6 months after the training. The primary outcome measure was the Fugl-Meyer Assessment-Upper Extremity (FMA-UE), supplemented by secondary outcome measures of the FMA-UE of the shoulder and elbow (FMA shoulder/elbow), the FMA-UE of the wrist and hand (FMA wrist/hand), the Modified Ashworth Scale (MAS), the Action Research Arm Test (ARAT), the Wolf Motor Function Test (WMFT), the Functional Independence Measure (FIM), as well as electromyography (EMG) and kinematic measurements. Twenty participants completed the telerehabilitation program, with 19 returning for a 3-month follow-up, and 18 for a 6-month follow-up. Significantly improved clinical scores were observed after the training (p ≤ 0.05). These improvements were maintained after 6 months in the FMA-UE, FMA shoulder/elbow, MAS at the wrist flexor, WMFT score, WMFT time, and FIM (p ≤ 0.05). The maintained improvements in motor function were attributed to reduced muscular compensation, as indicated by EMG and kinematic parameters. The WH-ENMS-assisted self-help telerehabilitation could achieve long-lasting rehabilitative effects in chronic stroke.